Neglected Ocular Trauma by Patient and Local Practitioner - Bhandari, Nirajan; Thapa, Bikram Bahadur (Journal of Nepalgunj Medical College, 2019)
Ocular trauma is the major cause of vision loss. The circumstances and agents implicated in such injuries are diverse. In context of Nepal, fall injury is most common form of accident. We present a case of penetrating ocular trauma in 30 years old house wife who fell from tree. The impacted wooden foreign body was removed on emergency basis. Delay in seeking specialty medical help by patients and ignorance of local practitioner for referral resulted in macerated conjunctiva. This case highlights the propensity of grievous ocular trauma in domestic environment.